Edukasi Tentang Sertipikat Tanah Digital di Era Transformasi Digital (Lembaga Pengembangan Kinerja Dosen, 2026)
Significant changes have occurred in the land administration sector with the introduction of digital land certificates as part of an ongoing digital transformation in public services. However, public understanding of the concept, procedures, and benefits of digital certificates is still relatively limited, leading to uncertainty and hesitation in their adoption. This community service program aims to increase public awareness and knowledge about digital land certificates through interactive education and structured socialization activities. The program includes seminars, guided discussions, and question-and-answer sessions designed to provide clear and practical explanations about how digital certificates function within the land registration system. As a result of these activities, community members become more informed about the advantages of digital certificates, such as greater efficiency, enhanced data security, improved transparency, and reduced risks of document damage or loss. This educational initiative is expected to strengthen public trust, encourage active participation, and support the more effective and sustainable implementation of digital land certificate services in the future.